Grafting of collagen onto interpenetrating polymer networks of poly(2-hydroxyethyl methacrylate) and poly(dimethyl siloxane) polymer films for biomedical applications - Z. A. Mohd Ishak; S. M. Rezaei (eXPRESS Polymer Letters)
Poly(dimethyl siloxane) (PDMS) films were modified using poly(2-hydroxyethyl methacrylate) (PHEMA) by sequential method of interpenetrating polymer networks (IPNs). Collagen (type I) was also linked onto the modified films via methyl sulfonyl chloride. Collagen reacted with the activated groups to obtain covalently linked protein layers. The surface properties of samples were characterised by attenuated total reflectance Fourier transform infrared spectroscopy (ATRFTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and water contact angle measurements. Dynamic Mechanical Thermoanalysis (DMTA) and tensile testing were used to study the physical and mechanical properties of the IPNs. Grafting of collagen on the surface was confirmed using ATR-FTIR and XPS. The results also showed that the hydrophilicity of modified samples increased as the content of PHEMA increased. The biocompatibility of the PDMS surface was evaluated by culture of fibroblast cells (L929). The collagen-linked surfaces showed significant cell adhesion and growth in comparison with unmodified PDMS samples.